2015
DOI: 10.1371/journal.pone.0117043
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Fetal Heart Rate Monitoring in Inpatient Full-Term Pregnant Women: Testing Functionality and Acceptability

Abstract: We tested functionality and acceptability of a wireless fetal monitoring prototype technology in pregnant women in an inpatient labor unit in the United States. Women with full-term singleton pregnancies and no evidence of active labor were asked to wear the prototype technology for 30 minutes. We assessed functionality by evaluating the ability to successfully monitor the fetal heartbeat for 30 minutes, transmit this data to Cloud storage and view the data on a web portal. Three obstetricians also rated fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Wireless devices for blood pressure (Microlife WatchBP) and cardiotocography (Sense4Baby, BMA-Telenatal, The Netherlands) were used for daily follow up of patients with either PPROM, FGR or preeclampsia [16,17]. Following a hospital admission for initial observation and treatment (e.g.…”
Section: Context Of the Feasibility Pilotmentioning
confidence: 99%
“…Wireless devices for blood pressure (Microlife WatchBP) and cardiotocography (Sense4Baby, BMA-Telenatal, The Netherlands) were used for daily follow up of patients with either PPROM, FGR or preeclampsia [16,17]. Following a hospital admission for initial observation and treatment (e.g.…”
Section: Context Of the Feasibility Pilotmentioning
confidence: 99%
“…Consequently, this technology may have the potential to reduce the rates of perinatal deaths. Wireless fetal heart monitors that transmit fetal heart rate data to a central server remotely either through modems [ 14 ] or Bluetooth [ 15 ] have been developed to allow real-time assessment of labour. Pilot studies have found the Bluetooth technology to be acceptable and feasible to both women and clinicians in both outpatient and inpatient settings of developed countries [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wireless fetal heart monitors that transmit fetal heart rate data to a central server remotely either through modems [ 14 ] or Bluetooth [ 15 ] have been developed to allow real-time assessment of labour. Pilot studies have found the Bluetooth technology to be acceptable and feasible to both women and clinicians in both outpatient and inpatient settings of developed countries [ 15 , 16 ]. The recorded CTGs from a wireless fetal monitoring prototype technology were also found to be easy to read generally and the technology itself useful, likeable and recommended among pregnant women in an inpatient labour ward in USA.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of fetal rhythm and diagnosis are typically performed using Doppler and M-mode echocardiographic techniques, 6 with newer modalities such as the developing fetal ECG and magnetocardiography available only in few centres. 7 Unfortunately, both modalities appear unsuitable for outpatient monitoring of fetal arrhythmia, and neither technology has the ability to record rhythms over long periods of time or to assess trends and changes in fetal heart rate. 8 Magnetocardiography may be able to record for longer periods of time; however, the technology is still cumbersome and available only to specialised referral centres.…”
mentioning
confidence: 99%